Influência da bacteriose foliar e a desfolha artificial em mudas de eucalipto no crescimento pós-plantio - Melo, Murilo Raphael de [UNESP] (2017)
Diseases are one of the factors that most contribute to decrease the Eucalyptus spp. productivity. Now a day observe the gradual increase of bacterial origin diseases, mainly of foliar occurrence. The bacterial leaf spot occurs in eucalyptus seedlings at all stages of nursery production, and it can easily take to the field, damaging the initial development of the seedlings. In this study was evaluated the effect of bacterial leaf spot severity and defoliation on post-planting growth of Eucalyptus seedlings. The evaluated plants presented a delay in the development due to disease and defoliation; however, maintaining the fertilization, after the recovery, the seedlings had their growth normalized.